Estudo da fototerapia de baixa potência no modelo de inflamação aguda induzida no joelho de ratos - Carlos, Fernando Pereira (2011)
The acute arthritis of the knee is a common joint disorder, and its prevalence increases in parallel with increasing age, is one of the most frequent causes of pain, loss of function and removal of work activities in adults. Many treatments are used to treat pain associated with rheumatoid arthritis. Nonsteroidal anti-inflammatory drugs (NSAIDs), anti-rheumatic drugs among others, cause adverse effects when used for prolonged periods, and are not effective in many patients. For this reason, it is the incessant search for new therapies to treat the arthritis. The physiological and noninvasive therapy, such as low level laser therapy (LLL), may be important in maintaining the inflammation and joint pain long term. Treatment with LLL has been introduced in clinical practice to treat inflammatory conditions. However, the mechanism of the effect of LLL in inflammatory processes is not fully elucidated. Thus, the aim was to study the effects of phototherapeutic treatment in acute arthritis induced by zymosan in the rat knee, looking to migration of inflammatory cells into the joint cavity, the release of proinflammatory mediators and metalloproteinase. Treatment with laser (660 nm) immediately, 1st and 2h after induction of inflammation significantly inhibited the influx of leukocytes into the joint cavity, the release of IL-1 and IL-6 and also the expression of matrix metalloproteinase-2 and 9. The treatment with LED (640 nm) decreased the influx of leukocytes, the expression of metalloproteinase but had no effect on the release of inflammatory cytokines. These results showed that the 685nm laser and LED have an anti-inflammatory effect in arthritis induced by zymosan, however the LED is not effective in reducing pro-inflammatory cytokines.